An optimized surface topography for calcium phosphate bone tissue engineering scaffolds - Mealy, Jacob Sebastian (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
Improved scaffold/host integration and avoiding core necrosis are important and active goals in tissue engineering. Alternatives to bone tissue grafting that are highly bioactive and inexpensive to manufacture are clinical necessities, particularly in relation to today’s ageing population profiles. There is also a need to develop such grafting alternatives for applications where tissue-engineered solutions (i.e. based on tissue growth in perfusion bioreactors) are not feasible from a clinical and cost perspective. Nanoscale surface topography has the potential to influence many aspects of cellular behaviour on tissue engineering scaffolds including proliferation. The aim of this project was to optimize the surface topography of a hydroxyapatite (HA) bone tissue engineering scaffold in order to increase mesenchymal stem cell (MSC) proliferation on the construct. The working hypothesis was that nanoscale features incorporated into the scaffold pore surfaces would provide a stimulus to increase cellular activity and overall proliferation. Two methods of surface manipulation were investigated; sintering temperature and nanophase addition. Cellular proliferation was indicated by MSC metabolic activity and was measured using a resazurin sodium salt media assay. Scaffold pore surfaces were modelled using lightly pressed, two-dimensional disks in order to remove confounding factors such as pore size and shape. Altering sintering temperature from 1100°C to 1350°C produced several surface morphologies: from small, granular features ~500nm in size at low temperatures, to smooth, glassy features ~10μm in size at high temperatures. Cells proved incapable of adhering to the low temperature surfaces (<1250°C) while the best proliferation rates were observed on the 1300°C and 1350°C samples. The average surface wavelength, λ, correlated strongly with cellular response to the surfaces. From this, a threshold wavelength of ≥2.4μm was suggested as being necessary for cellular adhesion. The best performing surfaces had wavelengths of ~2.65μm. The necessity for a relatively long surface wavelength to facilitate adhesion led to the design of an idealised surface with an underlying basal layer of appropriate wavelength, into which would be embedded nanoscale features to stimulate proliferation. This design was realised through the addition of an alumina nanopowder to the HA precursor in concentrations of 1-10wt%. The resulting topography closely matched the target design and proved capable of increasing cellular proliferation by 261.5% over pure HA. These results translated well to full, three-dimensional scaffolds, proving the applicability of the technique in a relevant, tissue engineering context. The novel construct, consisting of HA+5wt% alumina, was compared to a market leading commercial scaffold as a benchmark test. Cellular proliferation was an order of magnitude higher on the novel formulation when compared with the commercial scaffold. Furthermore, ELISA tests revealed that IL-1β expression in both macrophages and dendritic cells in response to the scaffolds was six times less on the novel formulation as on the commercial comparator. This shows that the novel scaffold induced a significantly lower inflammatory response compared to an existing therapy. These results prove the superior in vitro performance of the novel topography and allow for the optimized scaffold to be taken forward to in vivo trials. The overall project aim was achieved by adding an alumina nanophase to HA bone tissue engineering scaffolds to produce an optimized surface topography that significantly increased cellular proliferation on the scaffold pores. This will improve the overall scaffold performance in vivo and help alleviate the effects of core necrosis. The novel construct has the advantage of using inexpensive materials and a manufacturing methodology that is easily scalable to industry.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin